The changing face of oral anticoagulants - Rider, O; Rider, E (British Dental Association, 2013)
Warfarin has been the established oral anticoagulant for the last 50 years, being effective in the prevention and treatment of venous and arterial thromboembolic disorders. However, the frequent requirement for INR monitoring, multiple drug and food interactions have fuelled the need for development of new oral anticoagulants. Dabigatran is the first of a series of new oral anticoagulants that are emerging as the successors to warfarin. This new group of anticoagulants is rapidly gaining FDA and NICE approval and has proven non-inferiority to warfarin and viable alternatives to warfarin in the coming years. Given the obvious impact of this on dental treatment in the primary care and hospital setting this article aims to increase familiarisation with this new medicine group.